Study of Stability and Power Quality of Grid-Connected Inverter for Vehicle-to-Grid Application - Choi, Wooyoung (My University, 2015)
The objective of this research is to investigate stability and power quality of a parallel grid-connected inverter system for vehicle-to-grid application. The grid-connected inverter system includes a voltage source inverter, output LCL filter, grid, and closed-loop controller. The inverter topology is IGBT-based three-phase two-level voltage source inverter and power controller and voltage oriented PI controller are used to regulate grid current. A state space model of single grid-connected inverter system is mathematically modeled in stationary and synchronous reference frame. Frequency response of grid current are also modeled and analyzed according to number of parallel grid-connected inverters and for different grid inductances. N-number of parallel grid-connected inverter system is modeled and analyzed in frequency domain. In this research, stability analysis of grid connected inverters is investigated by assessing closed loop poles of system. Instantaneous total harmonic distortion of grid current is examined to analyze power quality of grid including FFT results of grid current. The dynamic simulation results obtained using MATLAB SIMULINK and SIMPOWER TOOL are used to demonstrate the importance of controller gain and grid conditions on system stability and power quality for a parallel grid-connected inverter system.